Online Attendance Management System - Kamalakkannan.P, Manikandan.V, Sankar.T (International Journal of Modern Agriculture, 2021)
Student attendance management system deal with the maintenance of the student’s attendance details. It is generates the attendance of the student on basis of presence in class. It is maintaining daily basis of attendance, the staff will be provide with the separate username and password to make student attendance. The staff handling the particular subject to responsible to make the attendance for all students. Only if the student presents the particular date, the attendance will be calculated. The student attendance report based on monthly and consolidate will be generated.